Exploring the Relationship between Environmental Cognition, Pro-Environmental Behavior, and Mental Health among Adolescents: A Narrative Review - Jacob, Leema; Reddy, K Jayasankara (Indian Journal of Community Health, 2024)
Introduction: Adolescents’ cognition, behavior, and attitudes are essential for environmental conservation; hence, the physical environment is inevitable in their mental health. The environment can influence adolescents’ sense of support, freedom, and the stimulation they seek in life. Environmental factors such as pollution, weather, lifestyle changes, and working conditions significantly influence adolescents' mental health. Knowing and learning about environmental cognition and its influence on adolescents is vital. Objective: To understand the relationship between environmental cognition, pro-environmental behavior, and mental health among adolescents with the help of a narrative approach. Methods: The present article ‘employed a narrative review.’ Research articles were taken from four databases, PubMed, Research Gate, Web of Science, and Science Direct, using the PRISMA procedure from 2000 to 2023. The data was collected from various databases and narrowed down for the results. Results: This study proves a strong relationship between environmental cognition, pro-environmental behavior, and adolescents' mental health. Twenty-six selected research studies out of 45 initial studies state that solid environmental cognition may lead to enhanced pro-environmental behavior, which is crucial to adolescents’ mental health and well-being. Furthermore, pro-environmental cognition wholly mediated the relationship between environmental behavior and mental well-being. Conclusion: Implications of this study concentrate on developing focused interventions, creating urban planning policies, and developing adolescent-friendly community designs, which are solid pillars for promoting mental health. Adolescents must be motivated to protect the environment to become pioneers of pro-environmental behavior.